Repetitive nerve stimulation on survival in amyotrophic lateral sclerosis - Zhu, Yahui; Bai, Jiongming; Li, Mao; Wang, Hongfen; Wang, Jiao; Huang, Xusheng (Frontiers in Neurology, 2023)
Objective No previous studies investigated the association between decrement of low-frequency repetitive nerve stimulation (LF-RNS) and amyotrophic lateral sclerosis (ALS) survival. We aim to study the relationship between decrement and survival in ALS. Methods Sporadic ALS patients diagnosed at the Department of Neurology, the First Medical Center, Chinese PLA General Hospital from January 2018 to December 2019 were enrolled in this study. Experienced neurologists followed up the participants regularly every 6 months until January 2022. A decremental response of 10% or greater at least in one muscle was considered positive. According to the decrement, the participants were divided into LF-RNS (+) and LF-RNS (−) groups. Results One hundred and eighty-one sporadic ALS patients were recruited in our study, including 100 males and 81 females. Among them, 10 cases (5.5%) were lost to follow-up, 99 cases (54.7%) died, and 72 patients (39.8%) were still alive at the last follow-up. The median survival time of all ALS patients in this study was 42.0 months. There was no significant difference of median survival in LF-RNS(+) group and LF-RNS(−) group (p = 0.159, Kaplan–Meier method). In multivariate Cox regression analysis, age of onset, diagnostic delay, and ALS Functional Rating Scale-Revised (ALSFRS-R) score were associated with ALS survival, but the decrement was not correlated with ALS survival (p = 0.238). Conclusion The decrement in accessory and ulnar nerves was not associated with the survival of ALS. The decrement of LF-RNS could not be an electrophysiological marker to predict ALS survival.